Implementasi Akad Ba’i Istishna dan Ba’i Taqsith pada Pembiayaan Kepemilikan Rumah (Non Bank) di Perumahan Islami Indonesia - Arman Paramansyah; Izul Abdillah; Dessy Damayanthi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
This study aims to analyze the application of istishna and ba'i taqsith contracts on bankless home ownership financing and to find out the advantages of each of these contracts. This research was conducted using qualitative research with descriptive analysis method, namely research by focusing on the implementation of istishna and ba'i taqsith contracts and showing a relationship between the financing of house ownership without the bank, then conducting a description to provide a clear picture. The results of the study conclude that the istishna contract in its application, namely the mustashni/customer, pre-orders the house to be ordered from the shani/maker by stating the raw material specifications, size and payment system at the beginning of the agreement and the handover of the building will be handed over in a tough manner. In the payment system there are 2 schemes, namely: In cash and credit, in credit financing for Indonesian Islamic Housing using a ba'i taqsith agreement. Namely a sale and purchase contract with a payment in installments at a certain time and is more expensive than the cash price. Credit calculation uses a 7% margin of cash and flat prices until the end of payment, there are no penalties for late payments and if there is default, deliberations will be held for the solution. The advantages of the ba'i istishna and ba'i taqsith contracts are the advantages of the istishna contract, it can change the design desired by the consumer and the advantages of the ba'i taqsith contract, can negotiate prices, late payment is not subject to fines, the benefits are greater than the cash price, and to educate the public about sharia credit.